Utilização de dados de reanálise na estimativa do potencial eólico bruto no estado do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The current global energy scenario is characterized by the search for alternative energy sources, among the options, wind power establishes itself as one of the most importante sources. There is great potential for the growth of wind energy sector, but needs further study, particularly in regions with wind suitable location for the installation of wind sites. The region of Pampa Gaucho is the subject of much speculation about his wind potential, however, is low number of surveys in the region, there are not many databases consistente wind. Therefore, this paper analyzes the wind database of meteorological reanalysis Climate Forecast System Reanalysis (CFSR) of it National Center for Environmental Prediction (NCEP). According to the theoretical basis, is rescued the history of wind energy, analyzing your current situation, knowing the mechanisms of generation and working of winds that drive turbines. It is developed a methodology to validate the data reanalysis the CFSR compared with the wind database of six stations of the Brazilian Institute of Meteorology (INMET) nearest to the Pampa Gaúcho region. Later is obtained from the data of meteorological reanalysis of the CFSR wind field maps of the entire state of Rio Grande do Sul, and compared these with the maps of the wind atlas of the state.
Keywords: Electrical engineering; Wind power; Alternative energy sources; CNPQ::ENGENHARIAS; Engenharia elétrica; Energia eólica; Fontes alternativas de energia